Growth resistance and resilience of mixed silver fir and Norway spruce forests in central Europe: Contrasting responses to mild and severe droughts. (24th June 2021) - Bottero, Alessandra; Forrester, David I.; Cailleret, Maxime; Kohnle, Ulrich; Gessler, Arthur; Michel, Dominic; Bose, Arun K.; Bauhus, Jürgen; Bugmann, Harald; Cuntz, Matthias; Gillerot, Loïc; Hanewinkel, Marc; et al.
Abstract: Extreme droughts are expected to increase in frequency and severity in many regions of the world, threatening multiple ecosystem services provided by forests. Effective strategies to adapt forests to such droughts require comprehensive information on the effects and importance of the factors influencing forest resistance and resilience. We used a unique combination of inventory and dendrochronological data from a long‐term (>30 years) silvicultural experiment in mixed silver fir and Norway spruce mountain forests along a temperature and precipitation gradient in southwestern Germany. We aimed at examining the mechanisms and forest stand characteristics underpinning the resistance and resilience to past mild and severe droughts. We found that (i) fir benefited from mild droughts and showed higher resistance (i.e., lower growth loss during drought) and resilience (i.e., faster return to pre‐drought growth levels) than spruce to all droughts; (ii) species identity determined mild drought responses while species interactions and management‐related factors strongly influenced the responses to severe droughts; (iii) intraspecific and interspecific interactions had contrasting effects on the two species, with spruce being less resistant to severe droughts when exposed to interaction with fir and beech; (iv) higher values of residual stand basal area following thinning were associated with lower resistance and resilience to severe droughts; and (v) larger trees were resilient to mild drought events but highly vulnerable to severe droughts. Our study provides an analytical approach for examining the effects of different factors on individual tree‐ and stand‐level drought response. The forests investigated here were to a certain extent resilient to mild droughts, and even benefited from such conditions, but were strongly affected by severe droughts. Lastly, negative effects of severe droughts can be reduced through modifying species composition, tree size distribution and stand density in mixed silver fir‐Norway spruce forests. Abstract : We examined mechanisms and stand characteristics underpinning the growth resistance (Rt), recovery (Rc) and resilience (Rs) to past mild and severe droughts in mixed silver fir and Norway spruce mountain forests in southwestern Germany. We found that the forests investigated were to a certain extent resilient to mild droughts, and even benefited from such conditions, but were strongly affected by severe droughts (especially those stands with higher residual basal area and larger trees). Lastly, negative effects of severe droughts can be reduced through modifying species composition, tree size distribution and stand density in mixed silver fir‐Norway spruce forests.